Food tourism: opportunities for SMEs through diaspora marketing?. Issue 2 (16th December 2021) - Bowen, Robert
Abstract : Purpose: The aim of this paper is to investigate the impact of the diaspora effect on food tourism. Focussing on the nexus of diaspora marketing, entrepreneurship and food tourism, this paper seeks to explore opportunities for food and drink small and medium-sized enterprises (SMEs) to engage in food tourism activities through diaspora marketing. Design/methodology/approach: As an investigation of an under-researched concept, this research uses mixed methods to develop a deeper understanding of diaspora effects on food tourism. This includes an online survey of 169 food producers, with 37 follow-up interviews. Research was conducted with food producing SMEs in Wales and Brittany, two culturally and geographically similar places, where both the food and drink and tourism industries are significant parts of the local economy. Findings: Two avenues for diaspora tourism are apparent, either through engaging with diaspora networks, such as expatriate networks located outside the country of origin, or through the reverse diaspora effect, of visitors experiencing products and then seeking to purchase them once returned to their countries. Both approaches depend on the ability for the food producer to sell their products to international buyers, as well as ensuring that international buyers had sufficient awareness of the products, which also links to a positive reputation for food. Originality/value: The paper aims to take a novel approach to the impact of diasporas on food tourism by considering the entrepreneurial activity of businesses in developing opportunities for food tourism through diaspora marketing. Distinctions are made from existing research by studying diaspora tourism from the business perspective.